TOURISTS SATISFACTION WITH GOA AS A HOLIDAY DESTINATION - Dhillon, Parminder Singh (The journal of contemporary issues in business and government, 2022)
Tourist’s satisfaction with a holiday destination is the key to its success and also determines the behavioural intentions of the tourists to revisit. The satisfaction of the tourists with the destination always remained a crucial topic for research, however, there has been a very limited investigation done on beach destinations in India. This paper is an attempt to identify the destination satisfaction attributes for the tourists in the State of Goa also called as the beach capital of India. A questionnaire based survey was conducted with a sample of 285 tourists visited Goa and stayed in different hotels and resorts. The results revealed overall satisfaction except with few destination attributes. The study will be useful for the destination marketing organisations to frame a suitable strategy for the overall satisfaction of the tourists in Goa.